2023
DOI: 10.1113/ep091236
|View full text |Cite
|
Sign up to set email alerts
|

More airway smooth muscle in males versus females in a mouse model of asthma: A blessing in disguise?

Abstract: Mouse models are helpful in unveiling the mechanisms underlying sex disparities in asthma. In comparison to their female counterparts, male mice are hyperresponsive to inhaled methacholine, a cardinal feature of asthma that contributes to its symptoms. The physiological details and the structural underpinnings of this hyperresponsiveness in males are currently unknown. Herein, BALB/c mice were exposed intranasally to either saline or house dust mite once daily for 10 consecutive days to induce experimental ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Finally, only female mice were used in this study, and it was not possible to exclude the influence of gender effect on the results of the study. In addition, some studies have shown that airway responsiveness to methacholine was higher in male mice [ 38 , 39 ]. So gender effect should be further investigated in the future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, only female mice were used in this study, and it was not possible to exclude the influence of gender effect on the results of the study. In addition, some studies have shown that airway responsiveness to methacholine was higher in male mice [ 38 , 39 ]. So gender effect should be further investigated in the future studies.…”
Section: Discussionmentioning
confidence: 99%
“…While airway distensibility was greater in females than males in BALB/c mice, an inverse trend was observed in C57BL/6 mice. Interestingly, we have recently demonstrated in BALB/c mice that the thickness of the epithelium and the content of airway smooth muscle were both greater in males than females [ 18 ], perhaps explaining the lower airway distensibility in the former in this mouse strain. A similar study should be conducted to investigate whether these structural features also vary with sex in C57BL/6 mice and whether they are associated with a sexual dimorphism in airway distensibility.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were anesthetized and put under general analgesia using ketamine (100 mg/kg) and xylazine (10 mg/kg), and then tracheotomized and connected to the flexiVent (FX Module 2, SCIREQ, Montreal, QC, Canada) as previously described [ 17 , 18 ]. They were ventilated mechanically at a tidal volume of 10 mL/kg with an inspiratory-to-expiratory time ratio of 2:3 at a breathing frequency of 150 breaths/min and with a positive end-expiratory pressure of 3 cmH 2 O.…”
Section: Methodsmentioning
confidence: 99%